How clonal are clones? A quest for loss of heterozygosity during asexual reproduction in Daphnia magna. (10th April 2019) - Dukić, Marinela; Berner, Daniel; Haag, Christoph R.; Ebert, Dieter
Abstract: Due to the lack of recombination, asexual organisms are predicted to accumulate mutations and show high levels of within‐individual allelic divergence (heterozygosity); however, empirical evidence for this prediction is largely missing. Instead, evidence of genome homogenization during asexual reproduction is accumulating. Ameiotic crossover recombination is a mechanism that could lead to long genomic stretches of loss of heterozygosity (LOH) and unmasking of mutations that have little or no effect in heterozygous state. Therefore, LOH might be an important force for inducing variation among asexual offspring and may contribute to the limited longevity of asexual lineages. To investigate the genetic consequences of asexuality, here we used high‐throughput sequencing of Daphnia magna for assessing the rate of LOH over a single generation of asexual reproduction. Comparing parthenogenetic daughters with their mothers at several thousand genetic markers generated by restriction site‐associated DNA (RAD) sequencing resulted in high LOH rate estimation that largely overlapped with our estimates for the error rate. To distinguish these two, we Sanger re‐sequenced the top 17 candidate RAD‐loci for LOH, and all of them proved to be false positives. Hence, even though we cannot exclude the possibility that short stretches of LOH occur in genomic regions not covered by our markers, we conclude that LOH does not occur frequently during asexual reproduction in D. magna and ameiotic crossovers are very rare or absent. This finding suggests that clonal lineages of D. magna will remain genetically homogeneous at least over time periods typically relevant for experimental work.